OCT for non-destructive examination of the internal biological structures of mosquito specimen - Naresh Kumar Ravichandran; Deokmin Jeon; Junsoo Lee; Jaeseok Park; Byeonggyu Jeon; Sangbong Lee; Pilun Kim; Kwang Shik Choi; Hee-Young Jung; Byoung-Ju Yun; Mansik Jeon; Jeehyun Kim (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
The Study of mosquitoes and their behavioral analysis are of crucial importance to control the alarmingly increasing mosquito-borne diseases. Conventional imaging techniques use either dissection, exogenous contrast agents. Non-destructive imaging techniques, like x-ray and microcomputed tomography uses ionizing radiations. Hence, a non-destructive and real-time imaging technique which can obtain high resolution images to study the anatomical features of mosquito specimen can greatly aid researchers for mosquito studies. In this study, the three-dimensional imaging capabilities of optical coherence tomography (OCT) for structural analysis of Anopheles sinensis mosquitoes has been demonstrated. The anatomical features of An. sinensis head, thorax, and abdomen regions along with internal morphological structures like foregut, midgut, and hindgut were studied using OCT imaging. Two-dimensional (2D) and three-dimensional (3D) OCT images along with histology images were helpful for the anatomical analysis of the mosquito specimens. From the concurred results and by exhibiting this as an initial study, the applicability of OCT in future entomological researches related to mosquitoes and changes in its anatomical structure is demonstrated.